On the Reception of Aristotle’s Rhetoric in Byzantium - Cichocka, Helena (Peitho. Examina Antiqua, 2012)
The paper deals with the reception of Aristotle’s definition of rhetoric (Rhet. I 1355b26–27) in several Byzantine commentators of Hermogenes’ and Aphthonius’ treatises. A justification of critical interpretation of this definition is to be found in the commentaries of Troilus and Athanasius (4th/5th century) as well as Sopatros (6th century) and Doxapatres (11th century), Maximus Planudes (13th/14th century) and several anonymous commentators. The Byzantine tradition has found Aristotle’s definition of rhetoric to be all too theoretical and insufficiently connected to practical activity, which Byzantium identified with political life.